2021
DOI: 10.1108/jaee-07-2020-0161
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal real activities, meeting earnings targets and firms' future operating performance: evidence from an emerging economy

Abstract: PurposeThis paper aims to examine the extent to which real earnings management (REM) is used in Jordan to meet zero or previous year's earnings, and how this impacts the subsequent operating performance of Jordanian firms.Design/methodology/approachThe study used a sample of 98 Jordanian listed firms over the 2010–2018 period. To test the research hypotheses, which are formulated in accordance with both, agency theory and signalling theory, multivariate regression is performed using a pooled OLS estimation. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
1
13
1
Order By: Relevance
“…In addition, the mean (median) of the board size is 8 (9), respectively, exhibiting the optimal size according to Lipton and Lorsch (1992). The mean (median) of board independence is 0.42 (0.44), respectively, compared with the 0.34 (0.28) documented by Alhaddad et al (2021), it can be concluded that Jordanian listed firms are becoming more independent than before. CEO-duality has a mean of 16%, indicating that about 84% of Jordanian firms are following the recommendations of the 2017 Jordanian Corporate Governance Code and separate the roles of chief executive officer and chairman.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…In addition, the mean (median) of the board size is 8 (9), respectively, exhibiting the optimal size according to Lipton and Lorsch (1992). The mean (median) of board independence is 0.42 (0.44), respectively, compared with the 0.34 (0.28) documented by Alhaddad et al (2021), it can be concluded that Jordanian listed firms are becoming more independent than before. CEO-duality has a mean of 16%, indicating that about 84% of Jordanian firms are following the recommendations of the 2017 Jordanian Corporate Governance Code and separate the roles of chief executive officer and chairman.…”
Section: Resultsmentioning
confidence: 70%
“…In addition, the mean (median) of the board size is 8 (9), respectively, exhibiting the optimal size according to Lipton and Lorsch (1992). The mean (median) of board independence is 0.42 (0.44), respectively, compared with the 0.34 (0.28) documented by Alhaddad et al (2021), it can be concluded that Jordanian listed firms The firm size ranges from 5.5 to 9.25, with a mean of 7.40, which is quite similar to the 7.79 reported in India by Raithatha and Ladkani (2022). Market to book ratio has a mean (median) of 1.38 (1.52), while Market capitalization ranges from 4.87 to 9.14.…”
Section: Descriptive Statisticsmentioning
confidence: 74%
See 3 more Smart Citations